Optimizing Patient‐centered Communication and Multidisciplinary Care Coordination in Emergency Diagnostic Imaging: A Research Agenda. (17th November 2015) - Sabbatini, Amber K.; Merck, Lisa H.; Froemming, Adam T.; Vaughan, William; Brown, Michael D.; Hess, Erik P.; Applegate, Kimberly E.; Comfere, Nneka I.
Abstract: Patient‐centered emergency diagnostic imaging relies on efficient communication and multispecialty care coordination to ensure optimal imaging utilization. The construct of the emergency diagnostic imaging care coordination cycle with three main phases (pretest, test, and posttest) provides a useful framework to evaluate care coordination in patient‐centered emergency diagnostic imaging. This article summarizes findings reached during the patient‐centered outcomes session of the 2015 Academic Emergency Medicine consensus conference "Diagnostic Imaging in the Emergency Department: A Research Agenda to Optimize Utilization." The primary objective was to develop a research agenda focused on 1) defining component parts of the emergency diagnostic imaging care coordination process, 2) identifying gaps in communication that affect emergency diagnostic imaging, and 3) defining optimal methods of communication and multidisciplinary care coordination that ensure patient‐centered emergency diagnostic imaging. Prioritized research questions provided the framework to define a research agenda for multidisciplinary care coordination in emergency diagnostic imaging.